This Side of the Law: Evaluating Citizens' Attitudes Toward Legal Compliance. (2nd July 2020) - Cann, Damon; Yates, Jeff
Abstract: A fundamental concern of government is getting citizens to comply with its laws and regulations. Yet, this topic has received relatively little attention in legal or social science scholarship. We explore the degree to which people are committed to the rule of law and legal obedience. We employ a structural equation model approach to assaying the factors that influence citizens' beliefs regarding the importance of complying with government rules. We find that citizens' perceptions on the legitimacy of legal institutions, justice system scandals, and social capital considerations can impact citizens' beliefs on the importance of obeying the law.